APPLICATION OF THE APPLICABLE REGULATIONS ON THE HANDLING OF FOREIGN REFUGEES IN THE MEDAN IMMIGRATION DETENTION HOUSE (RELEVANCE OF PRESIDENTIAL REGULATION NUMBER 125 OF 2016) - Danni Ronaldo Simamora; T Riza Zarzani; Rahul Ardian Fikri (PT. Sinergi Legal Publisher, 2024)
This study discusses the implementation of Presidential Regulation (Perpres) Number 125 of 2016 on the handling of foreign refugees at the Medan Immigration Detention Center. Indonesia, as a transit country for international refugees, faces various challenges in handling the increasing number of refugees from Afghanistan, Myanmar, Sri Lanka, Somalia, and other countries. This study uses a normative legal method, by analyzing the legal framework, especially the relevance of Perpres No. 125 of 2016, which is the basis for government policy in providing protection and management of refugees. The results of the study show that the policy of handling refugees in Indonesia still faces a number of obstacles, including the lack of facilities and infrastructure, limited human resources, and budget support. Although Presidential Regulation No. 125 of 2016 is an important legal guideline, its implementation at the Medan Immigration Detention Center is considered not yet fully effective. This Presidential Regulation has not been able to accommodate the needs of refugees comprehensively, especially in terms of human rights protection, social integration, and providing access to education and health. This study recommends strengthening international cooperation with UNHCR and IOM, improving coordination between agencies, and optimizing the role of local governments in providing adequate facilities and protection for refugees. With the implementation of more effective policies oriented to human rights principles, it is hoped that the handling of refugees at the Medan Immigration Detention Center can run better and more sustainably.